Behavior of new forage sorghum progenies for the Semi-Arid region of Pernambuco, Brazil - Lira, Mário de Andrade; Araújo, Marcelo Renato A. de; Maciel, Gabriel Alves; Freitas, Erinaldo Viana de; Arcoverde, Augusto Sálvio S.; Leiming, Glória (Pesquisa Agropecuaria Brasileira, 2014)
This work is related to 45 recently developed forage sorghum varieties. It aims to offer to Pernambuco Semi-Arid region farmers forage sorghum (Sorghum bicolor L.) varieties with higher yield capacity. The trials were carried out in Caruaru, São Bento do Una, Arcoverde and Serra Talhada involving nine different environments made up with combinations of years and localities. The experimental design was in randomized blocks with three replications in 1982, and without replications in 1983 and 1984. Analysis of dry matter (DM) productivity stability was also realized using the linear regression coefficient following the Eberhart & Russel Model. Progenies 467-4-2, 380-5-1, 322-1-3 and 484-1-1 showed outstandig behavior across the environments. The two first ones yielded 12.47 and 11.45 t/ha of DM and had a linear regression b = 1.03. The last two ones yielded 10.67 and 10.49 t/ha of DM and had a linear regression b = 0.90, which characterizes them as adapted to a less favorable environment. The sorghum variety IPA 7301218, previously recommended for planting in Pernambuco, had inferior performance among all other treatments.